How Well Do Aggregate Bank Ratios Identify Banking Problems? - Cihak, Martin (IMF Working Papers; Working Paper, 2007)
The paper provides an empirical analysis of aggregate banking system ratios during systemic banking crises. Drawing upon a wide cross-country dataset, we utilize parametric and nonparametric tests to assess the power of these ratios to discriminate between sound and unsound banking systems. We also estimate a duration model to investigate whether the ratios help determine the timing of a banking crisis. Despite some weaknesses in the available data, our findings offer initial evidence that some indicators are precursors for the likelihood and timing of systemic banking problems. Nevertheless, we caution against sole reliance on these indicators and advocate supplementing them with other tools and techniques.